Menciptakan Dunia yang Lebih Adil melalui Pendidikan - Siti Rohmah Nurhayati (Dinamika Pendidikan, 2008)
The   civilization growth of mankind    has   shown   the   existence of inequality between woman and men status.  This is caused  by difference of  treatment   between women   and  men  since  they  were  born.   Many efforts  conducted  to solve  the problem  of gender  inequality.   One of  the way to solve the problem   is developing gender fair education.   The goal of gender fair education   is   to reach equity  and equality  of gender  at performance of national education   development.  It consists equity  and equality  of gender  in aspects  of" ( 1) education  strategic environment; (2) justice  and generalization   of education;  ( 3) quality  and relevance of education;  and ( 4) education management.   Keyword: developing  gender fair  education